Unveiling complete natural reductive dechlorination mechanisms of chlorinated ethenes in groundwater: insights from functional gene analysis - Zhang, Zhuanxia; Ali, Mukhtiar; Tang, Zhiwen; Sun, Qi; Wang, Qing; Liu, Xin; Yin, Lipu; Yan, Song; Xu, Minmin; Coulon, Frederic; Song, Xin (Elsevier, 2024)
Monitored natural attenuation (MNA) of chlorinated ethenes (CEs) has proven to be a cost-effective and environment-friendly approach for groundwater remediation. In this study, the complete dechlorination of CEs with formation of ethene under natural conditions, were observed at two CE-contaminated sites, including a pesticide manufacturing facility (PMF) and a fluorochemical plant (FCP), particularly in the deeply weathered bedrock aquifer at the FCP site. Additionally, a higher abundance of CE-degrading bacteria was identified with heightened dechlorination activities at the PMF site, compared to the FCP site. The reductive dehalogenase genes and Dhc 16 S rRNA gene were prevalent at both sites, even in groundwater where no CE dechlorination was observed. vcrA and bvcA was responsible for the complete dechlorination at the PMF and FCP site, respectively, indicating the distinct contributions of functional microbial species at each site. The correlation analyses suggested that Sediminibacterium has the potential to achieve the complete dechlorination at the FCP site. Moreover, the profiles of CE-degrading bacteria suggested that dechlorination occurred under Fe3+/sulfate-reducing and nitrate-reducing conditions at the PMF and FCP site, respectively. Overall these findings provided multi-lines of evidence on the diverse mechanisms of CE-dechlorination under natural conditions, which can provide valuable guidance for MNA strategies implementation.
Keywords: Chlorinated ethenes; Natural reductive dechlorination; RDase genes; Groundwater